Binding of the D3-preferring antipsychotic candidate F17464 to dopamine D3 and D2 receptors: a PET study in healthy subjects with [11C]-(+)-PHNO. - Slifstein, Mark; Abi-Dargham, Anissa; Girgis, Ragy R; Suckow, Raymond F; Cooper, Thomas B; Divgi, Chaitanya R; Sokoloff, Pierre; Leriche, Ludovic; Carberry, Patrick; Oya, Shunichi; Joseph, Simon K; Guiraud, Marlène; et al. (Psychopharmacology, 2020)
Rationale: F17464, a dopamine D3 receptor antagonist with relatively high D3 selectivity (70 fold vs D2 in vitro), exhibits an antipsychotic profile in preclinical studies, and therapeutic efficacy was demonstrated in a randomized placebo-controlled clinical trial in patients with schizophrenia (Bitter et al. Neuropsychopharmacology 44(11):1917–1924, 2019). Objective: This open-label study in healthy male subjects aimed at characterizing F17464 binding to D3/D2 receptors and the time course of receptor occupancy using positron emission tomography (PET) imaging with a D3-preferring tracer, [11C]-(+)-PHNO. Methods: PET scans were performed at baseline and following a single 30 mg or 15 mg dose of F17464 (3 subjects/dose), and blood samples were collected for pharmacokinetic analysis. Receptor occupancy was calculated based upon reduction in binding potential of the tracer following F17464 administration. The relationship between plasma F17464 concentration and D3/D2 receptor occupancy was modeled and the plasma concentration corresponding to 50% receptor occupancy (EC50) calculated. Results: Both doses of F17464 robustly blocked [11C]-(+)-PHNO D3 receptor binding, with substantial occupancy from 1 h post-administration, which increased at 6–9 h (89–98% and 79-87% for the 30 mg and 15 mg groups, respectively) and remained detectable at 22 h. In contrast, D2 binding was only modestly blocked at all time points (< 18%). F17464 exhibited a combination of rapid peripheral kinetics and hysteresis (persistence of binding 22 h post-dose despite low plasma concentration). The best estimate of the EC50 was 19 ng ml−1 (~ 40 nM). Conclusion: Overall, F17464 was strongly D3-selective in healthy volunteers, a unique profile for an antipsychotic candidate drug.